QUANTUM TEACHING DAN APLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Badrus Zaman (Wahana Islamika: Jurnal Studi Keislaman, 2020)
n its development, models, approaches, strategies, and learning methods used in PAI learning, especially in formal educational institutions, are only operational and technical in nature so that PAI learning material experiences involution or delivery of PAI material which is static and monotone. PAI approaches, strategies and methods must be interrelated with vision, materials, curriculum, infrastructure, and educational evaluation in order to obtain optimal quality, so that PAI learning carried out in formal and non-formal educational institutions is able to provide a theoretical basis for the concept of PAI so that PAI learning experiences development and transformation for the better. The research model is library research, research data from primary sources and secondary data. Then the data is processed by content analysis. The conclusion of this study is the application of quantum teaching in PAI learning can be seen in 8 key advantages that exist in quantum teaching, 8 keys provide a useful way to get harmony and cooperation. The 8 keys set a framework for an environment of mutual support and trust where each student is valued and respected. So learning can take place without a threat. The 8 keys to excellence are: Integrity (honesty), initial failure of success, speak with good intentions, live at the moment, commitment, responsibility, flexible and balance.